Spectrum of electron-hole pair in quantum dots of a semiconductor nanolaser: theory - Pokutnyi, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
A theory of laser generation on size-quantization levels in semiconductor quantum dots put in a semiconductor matrix is developed. The size of quantum dots mass of which comprises the active sphere of an injection laser is determined by the new optical method consisting of the comparison of theoretical and experimental dependence of the spectrum of an electron-hole pair upon the radius of a quantum dot.